The impact of SEPA in credit transfer payments: Evidence from the euro area - Silva, V.G. (2017)
This paper analyses the effect of the implementation process of the Single Euro Payments Area (SEPA) project on credit transfer payments in euro area countries during the period between 2008 and 2013.